Product Lifecycle Management as a Tool to Create Value in the Fashion System. (13th August 2013) - D'Amico, Simona; Giustiniano, Luca; Nenni, Maria Elena; Pirolo, Luca
The aim of this paper is to present the fashion system as a "cluster" and to evaluate the characteristics of Product Lifecycle Management (PLM) taking into account various factors, in particular the different approaches to dealing with market needs. More specifically, the "ready-to-wear fashion" and "fast fashion" models will be presented and compared. The paper takes the Italian fashion system as the unit of analysis and assumes that consumer behavioural factors act in a non-predictable (i.e., random) way in the constantly changing social and cultural environment. Considering the internal complexity of a whole market system, a simplified system dynamics model is proposed.